Dietary phosphorus supplementation in the diet of Pacific white shrimp (Litopenaeus vannamei) alleviated the adverse impacts caused by high Clostridium autoethanogenum protein. Issue 131 (December 2022) - Zheng, Chaozhong; Cao, Junming; Chi, Shuyan; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Tan, Beiping
Abstract: The study evaluated the effects of dietary phosphorus supplementation on the fishmeal replacement with Clostridium autoethanogenum protein (CAP) in the diet of L. vannamei . Four isonitrogenous and isolipid diets were formulated: the PC diet contains 25% fishmeal, the NC, P1 and P2 diets were replaced 40% fishmeal with CAP and supplemented with 0, 0.8 and 1.6% NaH2 PO4 respectively (equivalent to dietary phosphorus level of 0.96%, 1.12% and 1.27%). Sampling and V. parahaemolyticus challenge test were conducted after 50-day-feeding (initial shrimp weight 1.79 ± 0.02 g). The results showed that there were no significant differences in the growth performance of shrimp among the 4 groups. The expressions of dorsal in the gut were significantly lower in shrimp fed the P1 and P2 diets than shrimp fed the NC diet and the expression of peroxinectin in the gut was lower in shrimp fed the NC diet than others. The cumulative mortality of shrimp after V. parahaemolyticus challenge was significantly lower in shrimp fed the P2 diet than those fed the NC diet. After the challenge, genes expressions related to the prophenoloxidase activating system ( proPO, lgbp, ppaf ) were inhibited in the hepatopancreas of shrimp fed NC diet but activated in shrimp fed the P1 diet compared to those fed the PC diet. The AKP and T-AOC activities were higher in shrimp fed the P2 diet than those fed the other diets. The thickness of muscle layer of shrimp fed the P1 diet was thicker than that in the other groups, and significant stress damage happened in the midgut of the shrimp fed the NC diet. The abundance of Pseudoalteromonas, Haloferula and Ruegeria in shrimp fed the P1 diet was higher than those fed the other diets, while Vibrio in shrimp fed the P2 diet was higher than those fed the other diets. This indicated that a low fishmeal diet with dietary phosphorus level of 1.12% could improve the histology, enhance immune response, and increase the abundance of beneficial bacteria in the gut of shrimp. The low fishmeal diet with dietary phosphorus level of 1.27% could improve disease resistance and antioxidant capacity, but there was a possibility of damage to the gut histology as well as increasing abundance of Vibrio in the gut microbiota of shrimp. Highlights: The feasibility of supplementing Dietary phosphorus based on the 40% fishmeal replacement with C. autoethanogenum protein in the diet of Pacific white shrimp. Dietary phosphorus level of 1.12% could improve the health of the gut of shrimp, while the level of 1.27% could enhance the disease resistance.